Catalytic pyrolysis of corn straw for deoxygenation of bio-oil with different types of catalysts - Zhang, Wenkai; Wang, Ze; Ge, Tengze; Yang, Cuiguang; Song, Wenli; Li, Songgeng; Ma, Rui (The Korean journal of chemical engineering, 2022)
Corn straw can be converted to bio-oil through pyrolysis. However, the application of bio-oil is severely restricted due to the high content of oxygen. Catalytic pyrolysis is an available way for deoxygenation of bio-oil, and the deoxygenation reactions are strongly dependent on the type of catalyst. Whereas, the correlation between the deoxy-genated products and the catalyst types is still far from clear. In this work, the migration of O in the pyrolysis process was investigated, and eight catalysts were screened for deoxygenation of bio-oil, with a lab-scale fixed-bed reactor. The results showed that with the increase of pyrolysis temperature, the content of O in bio-oil decreased below 400 °C and then became stable and finally increased rapidly after 550 °C, indicating that the range of 400–550 °C was the proper temperature for deoxygenation. Eight catalysts (ZSM-5, SAPO-34, ZnO, MgO, δ -Al 2 O 3 , γ -Al 2 O 3 , acidified- α -Al 2 O 3 and acidified- γ -Al 2 O 3 ) were tested, and it was found that a higher alkalinity of catalyst was favorable for decarboxylation of bio-oil with more produced CO 2 , while a higher acidity was promoted the decrease of alcohols and carbonyls with more generation of H 2 O and/or CO. MgO was judged as the optimal catalyst for deoxygenation of bio-oil. The quality of bio-oil under the catalysis of MgO was best, with higher H/C and lower O/C.